RETROSPECTIVE STUDY ON SEROPREVALENCE OF BORRELIA BURGDORFERI IN ELK AND MOOSE IN MINNESOTA - A. Z. Durrani; S. M. Goyal (Journal of Animal and Plant Sciences, 2011)
The database of the Veterinary Diagnostic Laboratory, University of Minnesota, was searched over a ten year period (2001-2010) to determine the seroprevalence of Borrelia burgdorferi (B. burgdorferi) in elk (Cervus elaphus) and moose (Alces americanus) in Minnesota, A total of 597 serum samples (62 from elk and 535 from moose) were tested for antibodies against B. burgdorferi using an indirect fluorescent antibody (IFA) test. Samples with titers of >1:320 were considered positive. Out of 597 sera tested, 135 (27%) were positive with IFA titers ranging between 1:320 and 1:1280. The rate of sero-prevalence was 52in elk and 19% in moose. These results indicate exposure of both species of cervidae to B. burgdorferi in Minnesota.
Keywords: Lyme disease; elk; moose; Borrelia burgdorferi; serologic survey.